2020
DOI: 10.18502/jpc.v8i2.3832
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine as Neuroprotective Potential Agent in Human and Animal Models: A Historical Overview

Abstract: Neurodegenerative disorders could be a most important health issue within the 21st century. In the recent past; there has been a growing interest in medicinal plants. Chemical fruits and vegetables are said to decrease the possibility of many chief ailments, together with cardiovascular and cancer disorders as well as neurodegenerative ailments. Hence, who eat more fruits and vegetables may be less threaten for developing certain diseases caused by neurological dysfunction. The present review provides an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In the brain, glabridin decreases the MDA level, and increases the superoxide dismutase level while reducing glutathione levels. A study suggested that G. glabra administration restored the decreased concentration of dopamine and glutamate in the brain and decreased activity of AChE [72]. decreases the enzymatic leakage of lactate dehydrogenase, preserves cellular morphology, restores superoxide dismutase, and catalyses enzyme levels, thereby preventing neuronal damage [77].…”
Section: Glycyrrhiza Glabramentioning
confidence: 99%
“…In the brain, glabridin decreases the MDA level, and increases the superoxide dismutase level while reducing glutathione levels. A study suggested that G. glabra administration restored the decreased concentration of dopamine and glutamate in the brain and decreased activity of AChE [72]. decreases the enzymatic leakage of lactate dehydrogenase, preserves cellular morphology, restores superoxide dismutase, and catalyses enzyme levels, thereby preventing neuronal damage [77].…”
Section: Glycyrrhiza Glabramentioning
confidence: 99%
“…that are highly studied and approved and they may be most reliable and useful. Second, utilizing natural anti-parasitic, antimicrobial, and anti-inflammatory medicines derived from plants, animals, and microbes (5,6). It has been concluded after studies that herbal medicines have efficiency in fighting against COVID-19 with activities in blocking the essential proteins for the life cycle of this virus (7).…”
Section: Introductionmentioning
confidence: 99%
“…The high antioxidant activity of ginger is due to the polyphenolic 6-gingerol compounds and its derivatives contained in these roots. [7] Another commonly used plant, Nigella sativa is a medicinal herb used for antioxidant activity. In rats, Nigella sativa seeds also play an important role in the lack of spatial cognition caused by chronic cerebral hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%